Field and laboratory observations on reproductive aspects of Pseudopaludicola ameghini (Cope, 1887) (Leptodactylidae: Leiuperinae) - Simioni, F.; Alves, N. C.; Picheli, K. O.R.; Pansonato, A.; Rossa-Feres, D. C. [UNESP]; Strüssmann, C. (Taylor & Francis, 2019)
The genus Pseudopaludicola includes small-sized anurans, widely distributed throughout South America. Twenty-three out of the 25 species occur in Brazil. Although described more than a century ago, from mid-southern Mato Grosso state, central Brazil, Pseudopaludicola ameghini is poorly known. Here we describe the characteristics of reproductive site, amplexus, egg-laying behaviour, eggs and tadpoles of P. ameghini based on specimens and observations performed in the vicinities of the type locality. Pairs of P. ameghini reproduce in shallow and slow groundwater established on hydromorphic terrains, in open environments amidst the Brazilian Cerrado savanna. Reproductive activity occurred between 17:00 and 21:00 h at two sites studied from December 2013 to April 2014. Amplexus is axillary. Eggs are spherical, with a mean diameter of 5.1 mm (yolk plus jelly envelope). Oviposition occurs in shallow sites at a depth of nearly 2.0 cm. Females deposit their eggs one at a time, directly onto sediment at the bottom of waterbodies or attached to submerged vegetation. The tadpole body is oval in dorsal view and globular/depressed in lateral view; eyes are large and dorsally positioned. Nares are large, round, with a small apophysis on marginal rim, dorsally positioned, near the eyes. The spiracle is short, with posterodorsal opening. The oral disc is anteroventral, emarginated laterally, with one dorsal and two ventral gaps; the tooth row formula is 2(2)/2(1), and the upper jaw sheath is ‘arc’ shaped. Pseudopaludicola ameghini has a unique behaviour of oviposition among members of the genus. The differences in reproductive pattern and larval characteristics of P. mystacalis and P. ameghini reinforce the taxonomic validity of the latter, questioned until recently.
Keywords: amplexus; Anura; Cerrado; reproductive behaviour